2014
DOI: 10.1536/ihj.13-322
|View full text |Cite
|
Sign up to set email alerts
|

Stent Thrombosis in Patients With Coronary Artery Disease Treated With Biodegradable Polymer Drug-Eluting Stents

Abstract: SummaryDelayed re-endothelialization may be the pathophysiological cause of stent thrombosis (ST). Biodegradable polymer drug-eluting stents (BP-DES) may reduce the risk of ST. The aim of this study was to evaluate the risk of ST in patients treated with BP-DES. Studies were retrieved from the PubMed, Cochrane Library, and EMBASE online databases. Twelve studies (15,155 patients) with long-term follow-up (≥ 12 months) were included. Compared with durable polymer drug-eluting stents (DP-DES), BP-DES did not sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…1,2) However, DES are associated with delayed arterial healing and persistent arterial inflammation that may increase the risk of stent thrombosis. [3][4][5] In particular, implanting DES in patients with ST-segment elevation myocardial infarction (STEMI) has been a controversial issue, because the lesions have high thrombogenicity and are potentially high risk for early stent thrombosis. 6,7) Recently, second-generation DES-everolimus-eluting stents (EES), biolimus-eluting stents (BES), and zotarolimus-eluting stents (ZES)-have been developed and used widely.…”
mentioning
confidence: 99%
“…1,2) However, DES are associated with delayed arterial healing and persistent arterial inflammation that may increase the risk of stent thrombosis. [3][4][5] In particular, implanting DES in patients with ST-segment elevation myocardial infarction (STEMI) has been a controversial issue, because the lesions have high thrombogenicity and are potentially high risk for early stent thrombosis. 6,7) Recently, second-generation DES-everolimus-eluting stents (EES), biolimus-eluting stents (BES), and zotarolimus-eluting stents (ZES)-have been developed and used widely.…”
mentioning
confidence: 99%
“…However, a recent meta-analysis showed a similar risk for definite and probable stent thrombosis between biodegradable polymer drug-eluting stents including BES and durable polymer drugeluting stents including SES and EES. 28) Finally, SES is no longer used in current clinical practice. However, the present propensity-score matched study has clearly demonstrated an advance in stent technology, by being the first to confirm overall better angiographic outcomes of EES and BES in comparison with the formerly approved, widely used, and evidencebased SES.…”
Section: Discussionmentioning
confidence: 99%
“…4,12,13) It seems that second-generation drug-eluting stents and biodegradable polymer drug-eluting stents might reduce stent thrombosis or restenosis. 14,15) However, the benefits of platelet function test guided therapy and whether identifying HTPR would led to interventions that reduced the risk of ischemic events are not certain.…”
Section: Discussionmentioning
confidence: 99%